Importance and challenges of geomagnetic storm forecasting - Khabarova, Olga; Price, Colin (Frontiers in Astronomy and Space Sciences, 2024)
Space weather prediction is a central focus of solar-terrestrial studies, with forecasts of geomagnetic storms deemed critical due to their significant practical implications. We have gathered facts that highlight the effects of geomagnetic storms on electric power systems and satellites. Recent studies indicate that geomagnetic storms of moderate intensity are statistically associated with larger spike amplitudes of telluric currents potentially leading to power outages compared to those caused by major storms. This underscores the importance of building reliable forecasts for all geomagnetic storms, especially given that solar cycles 20–24 saw less than 1% of storms classified as severe or extreme. A major challenge in current prediction models, even those utilizing advanced machine learning techniques, is the decline in accuracy for forecast lead times beyond 3 h, limiting the ability to mitigate infrastructure damage effectively. In this work, we provide a concise overview of geomagnetic storm statistics, describe key forecasting methods, recent advancements, and discuss the challenges in achieving accurate and timely storm predictions.